LEGAL ISSUES IN IMPLEMENTING THE EXECUTION OF FIDUCIARY COLLATERAL OBJECTS POST THE ISSUANCE OF THE DECISION OF THE CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA NUMBER 2/PUU-XIX/2021 - Edytiawarman; Fithriah, Nurhani; Arso, Dimas Dwi (Universitas Bengkulu, 2025)
This study aims to find out and analyze legal protection and certainty over the rights of parties for creditors in Fiduciary guarantees after the Constitutional Court Decision Number 2/PUU-XIX/2021, as well as the process of executing Fiduciary collateral objects by creditors in post-Fiduciary guarantees. Issuance of Constitutional Court Decision Number 2/PUU-XIX/2021. The research method was carried out in a normative juridical manner. The data used is secondary data obtained using a literature study. It is hoped that the research results can serve as input for decision-makers and the public in general related to legal issues in the execution of fiduciary guarantee objects after the issuance of the Ruling of the Constitutional Court of the Republic of Indonesia Number 2/PUU-XIX/20 Based on the results of the research, it can be concluded (1) Legal protection and legal certainty for the rights of Creditors (Fiduciary Recipients) after the issuance of the Constitutional Court Decision Number 2/PUU-XIX/2021, June 8, 2021, has undergone changes that lead to a potential for less guaranteed protection law and legal certainty of the rights of creditors (Fiduciary Beneficiaries) in exercising their rights to execute collateral Objects. (2) The process of executing Fiduciary collateral objects after the issuance of the Constitutional Court Decision Number 2/PUU-XIX/2021, June 8, 2021, can be carried out in 2 (two) ways, namely by submitting an application to the District Court and by parate executie as long as it has been there is an agreement regarding default/default since the guarantee agreement was made. The debtor voluntarily surrenders the Collateral Object to be executed. Keywords: Collateral, Constitutional Court Decision, Execution, Fiduciary, Legal Issues.